[PP.16.24] INFLUENCE OF STRESS AND ANXIETY ON BLOOD PRESSURE LEVELS IN PATIENTS UNDERGOING ORTHOPEDIC SURGERY. (September 2017) - Koutsaki, M.; Kallistratos, M.S.; Soulioti, E.; Kouremenos, N.; Vergis, K.; Koukouzeli, A.; Diakoumakou, O.; Mascha, O.; Mela, A.; Manolis, A.J.
Abstract : Objective: High blood pressure levels represent a common reason for postponing a scheduled surgery and are usually based on in hospital blood pressure (BP) measurements. Stress and anxiety of surgery regardless of the severity of the surgical operation, represents a significant factor that can influence BP levels. This study had the purpose to confront office BP levels with ambulatory BP (ABPM) measurement as well as cortisol levels, in order to evaluate the influence of stress and anxiety on BP levels, as well as to assess the variability of BP during surgery. Design and method: We present the results of a prospective observational study that enrolled 50 subjects undergoing scheduled orthopedic surgery. In all patients' office BP (1day before before surgery), ABMP (12 hours before and 12 hours after surgery as well as plasma cortisol levels (1 hour before and 24 hours after surgery) were measured. Results: present data of the perioperative period (before and after surgery), of a total 50 patients with mean age 73.8 ± 7.3 years. Mean office blood pressure levels (140/81 mmHg) were significantly greater from ABPM measurements 4 and 1 hours before surgery (122 ± 16, 9/72 ± 11 mmHg and 124 ± 21/71 ± 15 mmHg for SBP/DBP respectively) and 8 hours post operatively (137 ± 31/ 79 ± 19 mmHg) p < 0.01. Patients < 75 years presented greater BP variability in confront to patients > 75 years (p < 0.001). Cortisol levels decreased significantly postoperatively as compared with operatively measures (10.3 ± 0.7 mcg/dL vs.14.9 ± 1.0 mcg/dL, p < 0.001). The degree of change of cortisol was similar in patients aged < or > than 75 years (p = 0.671), while both operatively (p = 0.700) and postoperatively (p = 0.769) cortisol levels were not different between the two age groups. Conclusions: There is a significant difference between office BP and ABPM measurement in patients undergoing a scheduled orthopedic surgery. This gap can be explained from anxiety as expressed by the increased cortisol levels. Physicians must take into consideration this gap before proceed to the therapeutic handling of patients with increase BP levels or postponing a scheduled surgery. ABPM may be a useful tool in this context.